Debt markets and analysis - Johnson, R. Stafford (Bloomberg financial series, 2013)
An accessible guide to the essential elements of debt markets and their analysis debt markets and analysis provides professionals and finance students alike with an exposition on debt that will take them from the basic concepts, strategies, and fundamentals to a more detailed understanding of advanced approaches and models